Pluripotent Stem Cell-Based Approaches to Explore and Treat Optic Neuropathies - Rabesandratana, Oriane; Goureau, Olivier; Orieux, Gaël (Frontiers in Neuroscience, 2018)
Sight is a major sense for human and visual impairment profoundly affects quality of life, especially retinal degenerative diseases which are the leading cause of irreversible blindness worldwide. As for other neurodegenerative disorders, almost all retinal dystrophies are characterized by the specific loss of one or two cell types, such as retinal ganglion cells, photoreceptor cells, or retinal pigmented epithelial cells. This feature is a critical point when dealing with cell replacement strategies considering that the preservation of other cell types and retinal circuitry is a prerequisite. Retinal ganglion cells are particularly vulnerable to degenerative process and glaucoma, the most common optic neuropathy, is a frequent retinal dystrophy. Cell replacement has been proposed as a potential approach to take on the challenge of visual restoration, but its application to optic neuropathies is particularly challenging. Many obstacles need to be overcome before any clinical application. Beyond their survival and differentiation, engrafted cells have to reconnect with both upstream synaptic retinal cell partners and specific targets in the brain. To date, reconnection of retinal ganglion cells with distal central targets appears unrealistic since central nervous system is refractory to regenerative processes. Significant progress on the understanding of molecular mechanisms that prevent central nervous system regeneration offer hope to overcome this obstacle in the future. At the same time, emergence of reprogramming of human somatic cells into pluripotent stem cells has facilitated both the generation of new source of cells with therapeutic potential and the development of innovative methods for the generation of transplantable cells. In this review, we discuss the feasibility of stem cell-based strategies applied to retinal ganglion cells and optic nerve impairment. We present the different strategies for the generation, characterization and the delivery of transplantable retinal ganglion cells derived from pluripotent stem cells. The relevance of pluripotent stem cell-derived retinal organoid and retinal ganglion cells for disease modeling or drug screening will be also introduced in the context of optic neuropathies.